Bond Between SSTT Confined Concrete and Ribbed Steel Reinforcement Bar - Muhd Fauzy, Sulaiman; Faisal, Amsyar; Ma, Chau Khun; Abdullah Zawawi, Awang; Wahid, Omar (UniSE Press Publication, 2017)
A study about bond strength of normal strength concrete (NSC) and Steel Strap Confining Technique (SSTT) confined NSC was presented. A series of 8 specimens pull-out test were carried out to investigate the bond strength of short embedment (5Db) in SSTT confined NSC. The concrete compressive strength was about 45 MPa meanwhile the 12mm diameter reinforcement tensile strength was about 500 MPa were used in the pull-out specimens. In order to determine the effects of lateral confinement pressure of steel strapping, three groups of different steel strap gap distance pull-out test were conducted and compared with control specimens and previous theoretical bond stress equation. It was found that SS-B pull-out specimen exhibited highest bond strength and about 40 percent higher compared with Cont-B specimen as lowest bond strength pull-out specimen in this study.